2021
DOI: 10.1093/milmed/usaa299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluorescent Light Energy for the Treatment of Acute Second-degree Burns

Abstract: Introduction The use of photobiomodulation has been proposed to improve wound healing for the last two decades. Recent development in photobiomodulation has led to the development of a novel biophotonic platform that utilizes fluorescent light energy (FLE) within the visible spectrum of light for healing of skin inflammation and wounds. Materials and Methods In this article, FLE was used in preliminary analysis on 18 case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Although scar morphology was not significantly different between FLE-treated and control groups in this dermal fibrotic mouse model, accelerated wound healing is advantageous in itself since is reduces the risk of infections that often complicate the healing process and increases the risk of developing chronic wounds or fibrosis, including HTS. These results complement recent studies investigating the effect of FLE on different phases of wound healing showing accelerated healing of chronic venous leg ulcers, diabetic foot ulcers, and pressure ulcers as well as acute second-degree burns [ 13 , 27 , 28 ], while highlighting a potential superior effect of FLE in the earlier stages of healing. Further studies are needed to clarify the effect of FLE on reducing the risk of development of scarring.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although scar morphology was not significantly different between FLE-treated and control groups in this dermal fibrotic mouse model, accelerated wound healing is advantageous in itself since is reduces the risk of infections that often complicate the healing process and increases the risk of developing chronic wounds or fibrosis, including HTS. These results complement recent studies investigating the effect of FLE on different phases of wound healing showing accelerated healing of chronic venous leg ulcers, diabetic foot ulcers, and pressure ulcers as well as acute second-degree burns [ 13 , 27 , 28 ], while highlighting a potential superior effect of FLE in the earlier stages of healing. Further studies are needed to clarify the effect of FLE on reducing the risk of development of scarring.…”
Section: Discussionsupporting
confidence: 87%
“…This enables the light to penetrate various layers of the skin and interact with endogenous chromophores, such as flavins/riboflavins, cytochrome c oxidase subunit IV, and nicotinamide adenine dinucleotide hydrogen [ 56 ], in different layers in a single treatment. Moreover, previous clinical studies investigating FLE therapy has reported the treatment as applicable, safe, and with few adverse effects [ 17 , 18 , 25 , 26 , 27 , 28 ], underlining few clinical implications for the use of FLE. For treatment of acute second-degree burns or chronic ulcers, patients did initially experience some pain in relation to the FLE treatment, which was, however, not considered extraordinary compared with the standard of care for these conditions [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were included in the clinical category ( Table 4 ) [ 75 , 76 , 77 , 78 , 79 ], totaling 64 patients with wounds of different etiologies that were evaluated before and after light application. One of these studies evaluated the effect of BL on 12 patients; the control group comprised 8 patients who were not irradiated [ 79 ].…”
Section: Resultsmentioning
confidence: 99%